Interdelivery Interval and Medically Indicated Preterm Delivery - Dude, Annie M.; Grobman, William A. (American Journal of Perinatology, 2019)
Objective The objective of this study was to examine whether a medically indicated preterm delivery is relatively more likely following longer interdelivery intervals.Study Design This is a case–control study of women with two consecutive deliveries of a live singleton at the same institution between 2005 and 2015, with the subsequent delivery occurring preterm. Preterm deliveries were classified as spontaneous if women delivered following preterm labor, preterm premature rupture of membranes, or placental abruption. Preterm deliveries were classified as medically indicated if women underwent delivery for fetal or maternal medical indications. Interdelivery interval was categorized as < 18, 18 to 59, and 60 months or more. Characteristics of women who had a medically indicated versus spontaneous preterm delivery were compared.Results Of the 1,276 women, 25.6% had a medically indicated preterm delivery and 74.4% had a spontaneous preterm delivery. Compared with women with an interdelivery interval of 18 to 59 months (of whom 25.7% had a preterm delivery for medical indications), women with a shorter interdelivery interval were less likely (19.3%), while women with a longer interdelivery interval were more likely (37.4%; p = 0.003) to have a medically indicated preterm delivery. This relationship persisted even when accounting for other factors.Conclusion Preterm deliveries are more likely to be medically indicated as the interdelivery interval lengthens.
Keywords: interdelivery interval; preterm birth; preterm labor